A case of invasive meningococcal disease presenting as myopericarditis. (November 2021) - Durkin, Simon M.; Britton, Clemency; Cooke, Graham S.; Mehta, Ravi
Highlights: Invasive meningococcal disease can present as myopericarditis. The physician should be aware of delayed reactive inflammation, which can be severe. Attention should be paid to diagnostic sampling of pericardial effusions. Prompt antimicrobial treatment is essential. Abstract: Background: Neisseria meningitidis is a universally-feared Gram negative diplococcus, and infection confers high rates of morbidity and mortality despite effective antimicrobial therapy. Invasive meningococcal disease most commonly presents with meningococcaemia or meningococcal meningitis. Case report: 72-year-old female, previously fit and well, was admitted with chest pain, and associated breathlessness and diarrhoea. The clinical picture was of a myopericarditis. Results: Initial electrocardiogram (ECG) changes and elevated troponin were consistent with myopericarditis. Neisseria meningitidis W135 was cultured from blood, and subsequently from cerebrospinal fluid (CSF). Leptomeningeal meningitis and ventriculitis was evident on magnetic resonance imaging (MRI) of the brain. Treatment was commenced with intravenous ceftriaxone. The clinical course was complicated by pneumonia, influenza A infection, and fatal pulmonary embolism. Conclusions: This case demonstrates the range of clinical features of invasive meningococcal disease, highlighting in particular that meningococcal bacteraemia can present clinically as myopericarditis, which may be present in a substantial proportion of cases. Prompt antimicrobial therapy, as well as an awareness of potential complications, are paramount in the clinical management of meningococcal myopericarditis.